Reliability of different building microgrids - Meng, Zihao (Nanyang Technological University, 2022)
With the implementation of the concept of smart microgrid and the increasing maturity of renewable energy and distributed generation technologies, how to use electricity more efficiently and environmentally friendly has become the focus of attention. Residential and commercial buildings consume 32% of total global energy, and when upstream indirect emissions are considered, they account for about 30% of total end-use energy-related CO2 emissions. Therefore, how to improve the efficiency of energy use in buildings and achieve the goal of nearly zero energy buildings (nZEB) has become a priority.